Competitiveness of the Roasted Pecel Seasoning Business as an Effort to Reduce the Risk of Metabolic Disease - Aini, Nurul; Anggraini, Ika Rizki; Alifatin, Aini (Jurnal Pengabdian Masyarakat Bestari, 2024)
Pecel chili sauce is a food whose main ingredient is peanuts as a complement to the vegetable menu [1].  The food processing industry is very much carried out by the community, especially by groups of mothers [2].  The pecel seasoning that is produced is different from what especially consuming vegetables.  Assistance efforts are made for these businesses to improve the quality of production and marketing. The mentoring method is by providing training, direct practice in making roasted pecel spices and more contemporary packaging practices. The results of this activity are that pecel seasoning comes with more contemporary packaging, the business has a P-IRT, marketing via social media and online shops.is usually available on the market. By using simple technology, we can produce pecel seasoning with a delicious, traditional taste. The advantage of this pecel seasoning product lies in processing the nuts without frying them in oil, namely using a roasting system. The roasting principle is applied with the consideration that this food is not high in fat, so that it is safe for consumption by children to adults, even people suffering from metabolic diseases, for example hypertension, cholesterol, etc. This business has quite good potential, considering that currently it is becoming a trend among people to live a healthy lifestyle.